Handbook of development economics - Chenery, Hollis Burnley; Srinivasan, T. N.; Behrman, Jere R.; Rodrik, Dani.; Rosenzweig, Mark R. (Amsterdam ; New York : North-Holland ; New York, N.Y., U.S.A. : Sole distributors for the U.S.A. and Canada, Elsevier Science Pub. Co., 1988)
This Volume I is divided into three parts: Economic Development - Concepts and Approaches; Structural Transformation; Human Resources and Labor Markets.
Vol. 3 edited by Jere Behrman and T.N. Srinivasan.
Vol. 5 edited by Dani Rodrik, Mark R. Rosenzweig.
Includes bibliographical references and index.
rpm 07/02/2019
Loans
Keywords: Economic development; Development economics